2013
DOI: 10.1016/j.scitotenv.2013.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Hazard-ranking of agricultural pesticides for chronic health effects in Yuma County, Arizona

Abstract: With thousands of pesticides registered by the United States Environmental Protection Agency, it not feasible to sample for all pesticides applied in agricultural communities. Hazard-ranking pesticides based on use, toxicity, and exposure potential can help prioritize community-specific pesticide hazards. This study applied hazard-ranking schemes for cancer, endocrine disruption, and reproductive/developmental toxicity in Yuma County, Arizona. An existing cancer hazard-ranking scheme was modified, and novel sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 36 publications
1
38
0
5
Order By: Relevance
“…40 The validity of this approach hinges upon the validity of the toxicity data. We used categories for carcinogenicity assigned by the Pesticide Program of the US EPA through 2012.…”
Section: Identification Of Hazardous Pesticidesmentioning
confidence: 99%
“…40 The validity of this approach hinges upon the validity of the toxicity data. We used categories for carcinogenicity assigned by the Pesticide Program of the US EPA through 2012.…”
Section: Identification Of Hazardous Pesticidesmentioning
confidence: 99%
“…Global exposure may also be estimated using pesticide usage statistics as a proxy (Environment Canada, 2006;Sugeng et al, 2013) or using model outputs (Engelman et al, 2012;Pisani et al, 2008;Roelofs et al, 2005). To the best of our knowledge, no detailed national or regional statistics on pesticide use are available for France, contrarily to other countries such as U.K. (Food and Environment Research Agency) or USA (United States Geological Survey).…”
Section: Routes Of Exposurementioning
confidence: 99%
“…In this context, the statistics of potential exposure reported herein may serve to target ASs for future research on pesticide effects on wild birds inhabiting cultivated farmlands. In particular they may refine risk ranking models (EFSA, 2012;Environment Canada, 2006;Sugeng et al, 2013) that use pesticide usage data as a proxy of exposure. (2) The gray partridge is likely to be another well documented case study together with the skylark Topping and Odderskaer, 2004;Topping et al, 2005).…”
Section: Field Databasementioning
confidence: 99%
“…In general, the APs of liquid and emulsifiable formulations are absorbed more readily than those formulated as powders, dusts or granules (Mieldazys et al, 2015). Epidemiological studies have suggested the role of some APs in agriculture-related activities in the occurrence of neurodegenerative disorders like Parkinson's disease (Tanner et al, 2011;Pezzoli and Cereda, 2013;Brouwer et al, 2015;Furlong et al, 2015) and Alzheimer's disease (Hayden et al, 2009), endocrine-disrupting effects (Cocco, 2002;Weiss, 2011), some cancers (Alavanja et al, 2004;Purdue et al, 2007;Collota et al, 2013;Sugeng et al, 2013), etc.…”
Section: Health Effects Of Dermal Exposure To the Apsmentioning
confidence: 99%